Concept of life in Autobiographical Prose of Ivan Bunin and Vladimir Nabokov - Larisa I. Shchelokova, Nadezhda S. Stepanova,Alfia I. Smirnova, Tatiana V. Kovaleva, (Opción, 2019)
The article identifies the content and structure of the life concept in autobiographical works of the first wave of Russian émigrés. The authors analyze the lexical and semantic features of the concept in the autobiographical prose of Ivan Bunin and Vladimir Nabokov via integrated approach, including a conceptual analysis of a literary text. It was proved that the concept fulfills sense-forming, plot-forming and genre-forming functions, reinforces moral rules, and reflects physical and moral challenges and spiritual dynamics of a personality. In conclusion, the concept life is a complex mental formation, subject to semantic and value variation in various discursive practices.